Preparation and properties of novel tung oil and linseed oil modified lignin phenolic resin. (15th March 2023) - Xu, Chunyu; Meng, Fuliang; Qin, Yuan; Zhang, Yimiao; Hu, Zhenguo; Jia, Yufei; Yuan, Xinhua
Abstract: Replacing petroleum‐based raw materials with renewable materials is now obviously more in line with the needs of sustainable development. In this work, lignin, tung oil and linseed oil were selected to prepare tung oil modified lignin based phenolic resin (T‐LPF) and linseed oil modified lignin based phenolic resin (L‐LPF). T‐LPF and L‐LPF were characterized by FTIR, DSC, DMA, TGA, universal testing machine, SEM, friction and wear tester and 3D profilometer. The results show that compared with PF and LPF, the introduction of tung oil and linseed oil can reduce the curing activity and increase the curing peak temperature. The modified T‐LPF and L‐LPF have better thermal stability and mechanical properties. Compared with PF and LPF, the tensile strength of T‐LPF is increased by 33.4% and 41.75%, while the flexural strength is increased by 26.86% and 38.27% with the flexural strain increased by 68.97% and 91.41%. The tensile strength of L‐LPF is increased by 21.18% and 28.76%, while the bending strength is increased by 10.86% and 20.84% with the bending strain increased by 52.41% and 72.66%. T‐LPF and L‐LPF have better wear resistance than PF. They can be potentially used as resin matrix of high‐performance composites and friction composites.